1999
DOI: 10.1108/eum0000000006673
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the formation of entrepreneurial teams: the key to rapid growth business?

Abstract: There is ample anecdotal evidence, as well as an emergent body of literature, which examines the role of entrepreneurial teams in the success and growth of businesses. Earlier research by the authors has demonstrated that the core competence required by founding entrepreneurs is the ability to build and manage relationships. Their more recent work suggests that this core competence must be based around a clear vision for the business. In other words, the founding entrepreneur must be able to build a team to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 25 publications
3
73
0
5
Order By: Relevance
“…Extant literature lists prior experience in the entrepreneurial field, technical expertise, and profound knowledge on a specialty that was missing from the team up to that point among the qualities founders wish their team members to have (Vyakarnam et al, 1999). This article adds resilience, openness to change, good cooperation skills, and passion for the project among the characteristics that might appeal to founders during candidate selection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Extant literature lists prior experience in the entrepreneurial field, technical expertise, and profound knowledge on a specialty that was missing from the team up to that point among the qualities founders wish their team members to have (Vyakarnam et al, 1999). This article adds resilience, openness to change, good cooperation skills, and passion for the project among the characteristics that might appeal to founders during candidate selection.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the temporal evolution of key elements of the entrepreneurial team formation process, namely the founders' selection rationale and social networks (Hoang & Antoncic, 2003;Leung et al, 2006), indicates that at different instances of a venture's trajectory different behavioral patterns might be exhibited. In this regard, Vyakarnam et al (1999) found that the team formation process unravels in two temporal phases; during the first phase team members are found serendipitously or approached through founders' own networks, whereas during the second one new members are acquired through either informal networks or a more standardized recruitment process.…”
Section: Research Question and Temporal Influencesmentioning
confidence: 99%
See 2 more Smart Citations
“…-l'intérêt pour les (petites et moyennes) entreprises à forte croissance a augmenté dramatiquement ces dernières années, en témoingne le nombre d'études récentes sur leurs caractéristiques et occurrence (Blixt, 1997 ;Gundry et Welsch, 2001 ;Johnson, Baldwin et Hinchley, 1997 ;Sexton et Seale, 1997 ;Vyakarnam, Jacobs et Handelberg, 1997) ;…”
Section: Introductionunclassified